Evaluasi Postur Kerja Petani Berdasarkan Foto Digital Rapid Entire Body Assessment (REBA) Dan Usia Dengan Keluhan Nyeri Punggung Bawah - I Gede Purnawinadi; Norlandha Jacob; Christa Vike Lotulung; Lovely Sepang (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
Abstract Low back pain (LBP) is a common world health problem that can cause activities to be limited due to negative impacts received by the body, especially the lumbar vertebrae. This study aims to determine the relationship between work posture and age with the incidence of LBP in farmers. The research method used an analytical observational research design with a cross-sectional approach. The sampling technique used was total sampling with a sample size of 80 respondents. The data collection process used the NPB questionnaire and the Rapid Entire Body Assessment (REBA). The results showed a non-significant relationship between the work position and the incidence of low back pain in farmers (p>0.05) but there was a significant relationship in a positive direction between age and the incidence of low back pain in farmers (p<0.05) with a correlation coefficient of 0.548. Farmers are expected to maintain an ergonomic work posture and as much as possible change positions or stretch while working in an effort to reduce the risk of low back pain. It is necessary to make an application or system through software to overcome or complete the limitations in REBA measurements which are currently only manually so that the recorded data is not only using digital photos but maybe through video recordings and analyzed automatically in the system computerized to measure angles and evaluate them automatically real-time. Keywords— age, pain, posture, REBA